2014
DOI: 10.7900/jot.2012may24.1969
|View full text |Cite
|
Sign up to set email alerts
|

Paragrassmann algebras as quantum spaces, Part II: Toeplitz Operators

Abstract: This paper continues the study of paragrassmann algebras begun in Part I with the definition and analysis of Toeplitz operators in the associated holomorphic Segal-Bargmann space. These are defined in the usual way as multiplication by a symbol followed by the projection defined by the reproducing kernel. These are non-trivial examples of spaces with Toeplitz operators whose symbols are not functions and which themselves are not spaces of functions.MSC (2000): 46E22, 47B32, 47B35, 81R05

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 9 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…This clarifies why the examples in [22] and [23] are anti-Wick quantizations even though they arise in a non-commutative context. The longer, explicit computations given in those references are not needed as we can now see.…”
Section: Theorem 61 the Toeplitz Quantization T Is An Anti-wick Quanmentioning
confidence: 59%
See 3 more Smart Citations
“…This clarifies why the examples in [22] and [23] are anti-Wick quantizations even though they arise in a non-commutative context. The longer, explicit computations given in those references are not needed as we can now see.…”
Section: Theorem 61 the Toeplitz Quantization T Is An Anti-wick Quanmentioning
confidence: 59%
“…In [22] P is the holomorphic Hilbert space, while in [23] the sub-algebra P re(θ) plays the role of P. …”
Section: Sketch Of Proofmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, he showed that the reproducing kernel in the Segal-Bargmann space has the standard properties. Moreover, in [9], Sontz introduced the analysis of Toeplitz operators in the associated holomorphic Segal-Bargmann space in this situation. These are defined in the usual way as multiplication by a symbol followed by the projection defined by the reproducing kernel.…”
Section: Introductionmentioning
confidence: 99%